Candidíase vulvovaginal recorrente: uma contribuição ao diagnóstico - Nico, Alcina Frederica; Gouvêa, Tegnus Vinicius Depes de; Costa, Rosane Orofino (Brazilian Journal of Sexually Transmitted Diseases, 1994)
Recurrent vulvovaginal candidiasis is a common disease of difficult treatment. Some recognized predisposing factors are hnown, however these factors are not present in the majority of these woman. Further on cellular immunity has a considerably importance in the pathogenesis ofthis disease. Literature review is presented. ln order to analyse the prevalence of recurrent vulvovaginal candidiasis, 132 records from patients were reviewed in Sexually Transmitted Diseases from Universidade Federal Fluminense were analysed in the period ofaugust/89 to september/92, ofthese, 39 were infected by Candida: considering that in 14 of these patients, the author had an opportunity of using the immunoperoxidase stainning as a diagnostic: having positivity in all cases, with easier visualization offungic elements if compared with the Papanicolau's technique. Clinicai symtoms, predisposing factors and associated infections were correlated. We noticed 66% ofthe patients showed leukorrhea and itching, 30% used oral contraceptives and 23% showed diabete mellitus in the family history.